The Effectiveness of Dynamic Mindset Training on Students' Buoyancy and Academic Self-Efficacy - Abdieh, Shahrazad; Delavarpour, Mohammadagha; Tabatabaee , Seyed Mosa; Moradi , Shahab (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This research aimed to determine the effectiveness of dynamic mindset training on the buoyancy and academic self-efficacy of secondary school students.Methods and Materials: The research method was quasi-experimental with a pre-test-post-test design, including three follow-up assessments. A total of 37 female high school students from District 1 of Tehran in the academic year 2023-2024 were selected using purposive sampling and were randomly assigned to experimental and control groups. Initially, both groups completed the Academic Buoyancy Questionnaire (Dehghanizadeh & Hossein Chari, 2013) and the Academic Self-Efficacy Scale (Morgan & Jinks, 1999) as pre-tests. The experimental group then participated in 10 sessions of dynamic mindset training, each lasting 90 minutes, while the control group received no intervention. Following the training, both groups underwent post-tests and follow-up assessments. Data analysis was conducted using repeated measures analysis of variance.Findings: The findings indicated a significant increase in post-test and follow-up scores for academic buoyancy and self-efficacy in the experimental group (p < 0.001).Conclusion: Therefore, it is suggested that dynamic mindset training be implemented to enhance students' academic buoyancy and self-efficacy.